Pathological Changes of Placenta in Intrauterine Fetal Death - Paul, Sanchita; Kalita, Abhijit (Journal of Maternal and Child Health, 2023)
Background: Examination of placenta is one of the most common investigations undertaken after a stillbirth and  is one of the most valuable. Examination of placenta can yield information that may be important in the immediate and later management of the mother and infant. The present study aims to evaluate the pathological changes in placenta in intrauterine fetal deaths. Subjects and Method: It is a cross sectional comparative study conducted in Jorhat Medical College and Hospital, Jorhat for a period of one year from July 2020 to June 2021. Total 144 placenta were collected that comprised of 72 cases of intra uterine fetal death and 72 controls were taken. The cases and controls were selected by systematic random sampling. Statistical correlation was carried out by using Student T test with SPSS software or statistical significance p value of less than 0.05 was considered. Results: Placental weight, diameter and umbilical cord length and diameter were found to be significantly decreased in fetal deaths (p <0.05). Intervillous fibrinoid, peri villous fibrinoid, calcification, syncytial knots, infarction were found to be significantly associated with intrauterine fetal deaths in this study (p <0.05). Conclusion: The present study shows that significant information can be gathered by placental examination in adverse fetal outcome and can be used to know the cause of death and further management and prevention in future. Keywords: intrauterine death, syncytial knots, calcification, intervillous fibrin, peri villous fibrin Correspondence: Sanchita Paul, house no. 129, Karimganj, Assam. Pin: 788710. Phone: 9678801472. Email: sanchitavortex@gmail.com